A PET study comparing receptor occupancy by five selective cannabinoid 1 receptor antagonists in non-human primates. (February 2016) - Hjorth, Stephan; Karlsson, Cecilia; Jucaite, Aurelija; Varnäs, Katarina; Wählby Hamrén, Ulrika; Johnström, Peter; Gulyás, Balázs; Donohue, Sean R.; Pike, Victor W.; Halldin, Christer; Farde, Lars
Abstract: There is a medical need for safe and efficacious anti-obesity drugs with acceptable side effect profiles. To mitigate the challenge posed by translating target interaction across species and balancing beneficial vs . adverse effects, a positron emission tomography (PET) approach could help guide clinical dose optimization. Thus, as part of a compound differentiation effort, three novel selective CB1 receptor (CB1 R) antagonists, developed by AstraZeneca (AZ) for the treatment of obesity, were compared with two clinically tested reference compounds, rimonabant and taranabant, with regard to receptor occupancy relative to dose and exposure. A total of 42 PET measurements were performed in 6 non-human primates using the novel CB1 R antagonist radioligand [ 11 C]SD5024. The AZ CB1 R antagonists bound in a saturable manner to brain CB1 R with in vivo affinities similar to that of rimonabant and taranabant, compounds with proven weight loss efficacy in clinical trials. Interestingly, it was found that exposures corresponding to those needed for optimal clinical efficacy of rimonabant and taranabant resulted in a CB1 R occupancy typically around ∼20–30%, thus much lower than what would be expected for classical G-protein coupled receptor (GPCR) antagonists in other therapeutic contexts. These findings are also discussed in relation to emerging literature on the potential usefulness of 'neutral' vs. 'classical' CB1 R (inverse agonist) antagonists. The study additionally highlighted the usefulness of the radioligand [ 11 C]SD5024 as a specific tracer for CB1 R in the primate brain, though an arterial input function would ideally be required in future studies to further assure accurate quantitative analysis of specific binding. Highlights: The receptor occupancy of five CB1 R antagonists was compared in non-human primates. Comparable exposure-CB1 R occupancy relations were found across chemical classes. CB1 R antagonists may share a low occupancy at clinically effective exposure. The PET radioligand [ 11 C]SD5024 may be useful for examination of occupancy of CB1 R.